Psychological and Somatic Symptoms of Anxiety and Risk of Coronary Heart Disease: The Health and Social Support Prospective Cohort Study - Nabi, Hermann (2009)
BACKGROUND: Despite evidence showing anxiety to be a negative emotion that can be accompanied by various psychological and somatic complaints, previous studies have rarely considered these two components of anxiety separately in relation to coronary heart disease (CHD) events. This study aims to examine the extent to which the psychological and somatic components of anxiety are predictive of CHD. METHODS: This is a prospective population-based cohort study of 24,128 participants (9830 men, 14,298 women) aged 20 to 54 years. Psychological and somatic symptoms were assessed at study baseline in 1998. Fatal and nonfatal CHD events during the following 7 years were documented from data on hospitalizations from the National Hospital Discharge Register and mortality records from the Statistics Finland Register. RESULTS: In men, unadjusted hazard ratios for CHD per one unit increase in mean score were 1.50 (95% confidence interval [CI], 1.21–1.87) for somatic symptoms and 1.04 (95% CI, .85–1.29) for psychological symptoms. After serial adjustment for sociodemographic characteristics, biobehavioral risk factors, and clinically significant symptoms of depression, these associations were completely attenuated. In women, the corresponding unadjusted hazard ratios were 2.25 (95% CI, 1.66–3.06) and 1.55 (95% CI, 1.12–2.13), respectively. The corresponding fully adjusted hazard ratios were 1.47 (95% CI, 1.04–2.06) and 1.24 (95% CI, .91–1.70). CONCLUSIONS: Somatic symptoms of anxiety were robustly associated with an increased risk of CHD in women. This finding lends support to the physiological pathway for the association between psychological factors, anxiety in particular, and CHD.